Стан глутатіонової ланки тіол-дисульфідної системи у пацієнтів із хронічним обструктивним захворюванням легень в умовах артеріальної гіпертензії - Тягла, Оксана Сергіївна; Тяглая, О. С.; Tyagla, O. S. (My University, 2019)
Метою дослідження була оцінка глутатіонової ланки тіол-дисульфідної системи у пацієнтів із хронічним обструктивним захворюванням легень при артеріальній гіпертензії. У рамках дослідження було обстежено 59 хворих, які були розподілені на 3 субкогорти: 23 хворих було з діагнозом гіпертонічна хвороба ІІ стадії і хронічне обструктивне захворювання легень ІІ стадії без клінічно значущої супутньої патології, середній вік 51,72±1,22 (49,33-54,09) року (гендерний склад: 22 чоловіка і 1 жінка), статус паління можна порівняти з хворими на хронічне обструктивне захворювання легень. Також обстежено 18 хворих гіпертонічною хворобою обох статей у віці від 33 до 67 років (середній вік 50,74±1,49 (47,81-53,76); співвідношення чоловіки/ жінки 17/ 83%), II стадії захворювання з рівнем артеріальної гіпертензії I-III ступеня, різного кардіоваскулярного ризику, без адекватної систематичної антигіпертензивної терапії. Целью исследования была оценка глутатионового звена тиол-дисульфидной системы у пациентов с хроническим обструктивным заболеванием легких при артериальной гипертензии. В рамках исследования было обследовано 59 больных, которые были распределены на 3 субкогорты: 23 больных было с диагнозом гипертоническая болезнь II стадии и хроническое обструктивное заболевание легких II стадии без клинически значимой сопутствующей патологии, средний возраст 51,72±1,22 (49,33-54,09) года (гендерный состав: 22 мужчины и 1 женщина), статус курения можно сравнить с больными хроническим обструктивным заболеванием легких. Также обследовано 18 больных с гипертонической болезнью обоего пола в возрасте от 33 до 67 лет (средний возраст 50,74±1,49 (47,81-53,76), соотношение мужчины/ женщины 17/83%), II стадии заболевания с уровнем артериальной гипертензии I-III степени, различного кардиоваскулярного риска, без адекватной систематической антигипертензивной терапии. Studying the initial role of oxidative stress in the pathogenesis of chronic obstructive pulmonary disease on the background of arterial hypertension gives prospects for adequate pharmacological correction of this comorbid pathology taking into account all pathogenetic aspects. This is due to oxidative stress which is the causative factor in the delicate balance of the thiol-disulfide system, and also triggers the launch of the caspase mechanism of neutrophil apoptosis with progression and mutual burdening of nosologies. The aim of the study was to evaluate the metabolism of a biologically active tripeptide (consisting of γ- glutamic acid residues, cysteine and glycinute) and thiol-disulfide balance in patients with chronic obstructive pulmonary disease and arterial hypertension. Material and methods. During the study we examined 59 patients. They were divided into 3 subgroups: 23 patients were diagnosed with stage II hypertension disease and stage II chronic obstructive pulmonary disease without a clinically significant concomitant pathology, average age 51.72±1.22 (49.33-54.09) years, gender composition: 22 men and 1 woman, smoking status can be compared with patients with chronic obstructive pulmonary disease. The 2nd group comprised 18 patients with hypertension disease of both sexes aged from 33 to 67 years (average age 50.74±1.49 (47.81-53.76), the ratio of men/ women 17/83%), stage II hypertension disease I-III degree, and different cardiovascular risk, without adequate systematic antihypertensive therapy.
Состояние глутатионового звена тиол-дисульфидной системы у пациентов с хроническим обструктивным заболеванием легких в условиях артериальной гипертензии
Condition of Glutationion Chain of the Thiol-Disulphide System in Patients with Chronic Obstructive Pulmonary Disease and Arterial Hypertension
Keywords: тіол-дисульфідна система; хронічне обструктивне захворювання легень; артеріальна гіпертензія; глутатіон; антиоксидантна система; тиол-дисульфидная система; хроническое обструктивное заболевание легких; артериальная гипертензия; глутатион; антиоксидантная система; thiol-disulfide system; chronic obstructive pulmonary disease; arterial hypertension; glutathione; antioxidant system